2000
DOI: 10.1115/1.1313530
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Offshore Platforms Under Subsidence—Part I: Approach

Abstract: This is the first of four companion papers that present a comprehensive assessment of the effect of sea floor subsidence on the Valhall complex of platforms. The study has included an estimate of the increase in platform failure probability as a function of increased subsidence. Subsidence raises the effective mean still water level and increases the potential for inundation of the deck for extreme storm conditions. Deck wave slam forces generate significantly greater platform loading and lead to: (a) higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It is suggested that the component method [45,46] or computational fluid dynamic method [28,[47][48][49] are to be utilized to calculate the wave-in-deck load in order to reduce the conservatism of the silhouette method. The risk of platform damage may be reduced via modification such as localized protection or relocation of exposed sensitive equipment or via procedures such as production shut-in and temporary evacuation during storm season [59,60]. Another method that was successfully performed was by jacking-up the platform in order to increase the air gap of platform [61].…”
Section: Probability Of Failurementioning
confidence: 99%
“…It is suggested that the component method [45,46] or computational fluid dynamic method [28,[47][48][49] are to be utilized to calculate the wave-in-deck load in order to reduce the conservatism of the silhouette method. The risk of platform damage may be reduced via modification such as localized protection or relocation of exposed sensitive equipment or via procedures such as production shut-in and temporary evacuation during storm season [59,60]. Another method that was successfully performed was by jacking-up the platform in order to increase the air gap of platform [61].…”
Section: Probability Of Failurementioning
confidence: 99%
“…It has been reported that many existing platforms are under danger due to seafloor subsidence. Gebara et al (2000) reported that some of the platforms in the Valhall field subsided by a depth of 3.2 m, which was further forecasted to increase. Similar seafloor subsidence has been reported in North Sea and Gulf of Mexico also.…”
Section: Introductionmentioning
confidence: 95%
“…Gebara et al assess the performance of the jacket platform under subsidence and perform ultimate strength and reliability analyses for four levels of sea floor subsidence [5]. The assessment process of building prestandards was studied also.…”
Section: Introductionmentioning
confidence: 99%